A Sensitive Electrochemical MUC1 Sensing Platform Based on Electroactive Cu-MOFs Decorated by AuPt Nanoparticles. Issue 8 (21st April 2020) - Li, Ya; Hou, Lina; Liu, Zhiling; Lu, Wenbo; Zhao, Man; Xiao, He; Hu, Tianjun; Zheng, Zhanfeng; Jia, Jianfeng; Wu, Haishun
Abstract : Mucin 1 protein (MUC1) is a well-known tumor marker overexpressed in a variety of human malignancies, and thus its highly selective and sensitive detection is significantly desired for clinical diagnostics. Herein, a sensitive electrochemical MUC1 sensing platform has been fabricated based on copper-based metal-organic frameworks (Cu-MOFs) decorated with gold-platinum alloy nanoparticles (AuPt NPs). Besides serving as a redox probe to avoid introducing extra redox media, the electroactive Cu-MOFs function as catalysts in the hydrogen peroxide reduction, resulting in electrochemical signal amplification. Meanwhile, AuPt NPs loaded on the Cu-MOFs mimic horseradish peroxidase to promote the reduction of hydrogen peroxide, giving rise to the secondary-amplified electrochemical signal. Moreover, the target MUC1 triggered catalytic hairpin assembly (CHA) further improves the sensitivity of the developed biosensor via the target recycling amplification. The constructed sensing platform displayed a desirable dynamic range between 10 fM and 10 nM in the MUC1 detection, with a sufficiently low limit-of-detection (3.33 fM). The current strategy of utilizing hybrid nanocomposite consisting of MOFs and alloy NPs and enzyme-free CHA provides a promising platform for the detection of biomarkers in the clinical diagnosis with high selectivity and sensitivity.